The UBUNTUfication of a 21st century transformative primary english classroom - Oliveira, Suzette Marina Antunes Duarte (2018)
This project targets on African oral tradition storytelling intermingled with the Ubuntu philosophy and traditional cultures (Varty, 2013) in primary school learning contexts, focusing on how oral traditional stories can be integrated into classroom practices as a means of transformation and of accommodating diversity to foster social cohesion and sustainable development (Battiste, 2005; Themane, et al., 2011). By encompassing oral traditional storytelling with an experiential communicative approach (Fernández- Corbacho, 2014), both strategies and materials, which take into account the Gamification Octalysis Framework (Chou, 2016), have been created and experimented in a 4th year primary school in Oporto. Departing on Chou’s (2016) Octalysis framework and how it can effectively be applied during the implementation of several gamification designs and practices, leading us to a greater understanding of how competitiveness fostered in gamified tasks can be favourable to Primary English learning. Moreover, it is the authors’ intention to tap into the core essence of classroom practice, by focusing on the gamified tasks which stimulated collaboration, communication, critical thinking and creativity, which are considered as the basis for 21st century skills (Duarte, & Cruz 2017). An ethnographic methodological approach, with triangulation of data collection tools (questionnaires, course books analysis grids, lesson plans, self-assessment worksheets and project works), was resorted. Gamified practices, which deal with South African cultural and linguistic varieties (Esteves, & Hurst, 2009) and 21st Century Learning skills, were analized. The main results show that the gamification approach can aid in the progression of dialogue, can promote cultural awareness and can expedite pupil’s cognitive and affective enthralment and engagement, fostering the development of these skills (Cruz, & Orange, 2016; Shatz, 2015).